Eruptive Keratoacanthomas In Hodgkin′s Disease - Pavithran K (Wolters Kluwer Medknow Publications, 1997)
A 38 year old man developed eruptive keratoacanthomas along with early signs and symptoms of Hodgikinâ€s disease. The simultaneous development of both diseases and their simultaneous disappearance following chemotherapy suggest that their association is more than a simple chance occurrence.